Evaluating Vygotsky-Based Professional Development Models for Islamic Educators - Alwy Ahmed Mohamed; Maisuna Mustapha Yahya; Muhammad Rehan Sabir (Amandemen: Journal of Learning, Teaching and Educational Studies, 2026)
In light of current pedagogical and technical problems, this study tackles the growing demand for effective teacher professional development (PD) models in Islamic education. Even while teachers have a crucial role as murabbi in influencing students' intellectual, moral, and spiritual growth, many professional development programs in Islamic institutions are still content-focused and lack a solid theoretical foundation. By analyzing the applicability and efficacy of Vygotsky's social constructivist theory as a framework for teacher professional development in Islamic education, this research aims to close this gap. The study aims to evaluate how Islamic educators' pedagogical competence and reflective practice can be enhanced through Vygotsky-based professional development models, specifically focusing on the concepts of the Zone of Proximal Development, scaffolding, and social interaction. The study employs a qualitative and conceptual research approach, including thematic analysis of pedagogical practices, as well as document analysis of current professional development programs, relevant literature, and Islamic educational sources. The results show that Vygotsky-based PD models are very compatible with Islamic educational ideas, including dialogic instruction, tarbiyah gradualiyyah, and collaborative learning (halaqah). These models support learner-centered teaching methods, professional collaboration, and enhanced instructional methodologies. The conversation emphasizes how incorporating social constructivist theory into Islamic teacher preparation promotes comprehensive education based on moral and spiritual principles while also enhancing pedagogical efficacy. The study comes to the conclusion that a workable and contextually appropriate framework for improving teacher preparation in Islamic education is provided by Vygotsky-based professional development.